Metaprofiling of the bacterial community in sorghum silages inoculated with lactic acid bacteria - Puntillo, Melisa; Peralta, Guillermo H.; Bürgi, María D. Milagros; Huber, Paula; Gaggiotti, Monica Del Carmen; Binetti, Ana G.; Vinderola, Celso Gabriel (Society for Applied Microbiology, 2022)
To characterize the fermentation process and bacterial diversity of sorghum silage inoculated with Lactiplantibacillus plantarum LpAv, Pediococcus pentosaceus PpM and Lacticaseibacillus paracasei LcAv.